234k views
4 votes
Which choice is equivalent to the expression below?
Square root of -18

Which choice is equivalent to the expression below? Square root of -18-example-1
User Jei
by
5.3k points

2 Answers

4 votes

Step-by-step answer:

sqrt(-18)

= sqrt((-1)*(9)*(2)

= sqrt((-1))*sqrt(9)*sqrt(2)

= i*3*sqrt(2)

=3i*sqrt(2)

User Richard Deeming
by
5.7k points
1 vote

Answer:

C

Explanation:

Using the rule of radicals


√(a) ×
√(b)
√(ab)

and
√(-1) = i

Given


√(-18)

=
√(9(2)(-1))

=
√(9) ×
√(2) ×
√(-1)

= 3 ×
√(2) × i

= 3i
√(2) → C

User Shankze
by
5.9k points